Comparing mothers' and fathers' reports on the non-resident father's contact with his children - Ragni Hege Kitterød; Jan Lyngstad (Statistics Norway, Research Department, 2013)
Analyses of contact frequency between non-resident fathers and children are often based on samples of non-resident fathers or resident mothers only. It is well established that non-resident fathers tend to report more contact than the resident mothers do, but it is less clear whether it matters which parent we ask when the aim is to explore predictors of father-child contact. Based on a high-quality Norwegian survey of ex-couples of parents living apart we find that the amount of monthly father-child contact, measured by overnight stays and visitation days, is largely associated with the same independent variables whether we use the non-resident fathers' or the resident mothers' answers, but some differences do appear. We observe more significant associations between father-child contact days and the independent variables based on the resident mothers' than the non-resident fathers' reporting. The mother's educational attainment and whether the father has children with more former partners have significant effects in the subsample of resident mothers but not in the subsample of non-resident fathers. We argue that future surveys should collect information from both parents. Using information from one parent only should be a last resort if more adequate data cannot be obtained.
Keywords: J12; J13; 330; Absent fathers; Discrepancy between mother's and father's reporting; Father-child contact; Fathers' role after separation; Parents living apart